Comparative Analysis of Data Mining Classification Methods in Predicting Credit Payments - Khansa Raefa, Nabila; Ayu Kamila, Diah; Wahyunengsih (KH. A. Wahab Hasbullah University, 2024)
Credit activities in the form of saving money from members, providing loans to members and managing existing funds are still intuitive and can cause errors in the credit process. So that this crediting process does not occur and can run smoothly, a payment prediction using data mining is needed. Therefore we conducted this research. The research method we use is the knowledge discovery in database process model, where this process is divided into several stages, namely selection, pre-processing or cleaning, transformation, data mining and evaluation.